DYNAMICS OF THE HUJJAH OF HADITH FROM THE CLASSICAL ERA TO CONTEMPORARY (Study of the Impact of Modernist Muslim Thought) - Ramadhan, M. Rizki Syahrul; Abdulloh, Abdulloh (Nabawi: Journal of Hadith Studies, 2023)
The debate about the hujjah (cogency) of hadith has been going on since the classical era but has found a new chapter in the contemporary era. Since the classical era rejected the hujjah of hadith because of its transmission factor, the contemporary era (the modernist group) discusses it with a very radical question: whether hadith can be used as hujjah. It is important to trace the causes of these differences to maintain the continuity of hadith studies, between classical and contemporary. This article traces it by focusing on identifying the impact of modernist Muslim thought on the contemporary theory of the hujjah of hadith. To do this, this research targets three data: the theory of the hujjah of hadith in the classical era, the theory in the contemporary era, and the thoughts of modernist Muslims. The first data was extracted from Maḥmūd Ṭaḥḥan's book, the second data was from the work of al-Idlibī and Jasser Auda, and the third data was summarized from three books: the works of Aḥmad Amīn, Abū Rayyah, and al-Sibā'ī. The first and second data were analyzed comparatively and then connected to the third data which was analyzed through content analysis. Through this, it is confirmed that the contemporary theory of the hujjah of hadith is the impact of modernist Muslim thought which doubts the validity of hadith, the authority of the Prophet, and the revelation of hadith. Two contemporary theories of the hujjah of hadith emerged as counter and evaluative responses to three themes that modernist Muslims doubt.[Perdebatan tentang kehujjahan hadis memang telah terjadi sejak era klasik, namun mendapati babak baru dalam era kontemporer. Jika diskusi di era klasik menolak kehujjahan hadis karena faktor transmisinya, era kontemporer (kelompok modernis) mendiskusikan hal itu dengan pertanyaan yang sangat radikal, yakni apakah hadis memang bisa dijadikan hujjah. Perbedaan itu penting dilacak penyebabnya untuk menjaga kesinambungan kajian hadis, antara klasik dan kontemporer. Artikel ini melacak hal itu dengan fokus pada identifikasi dampak pemikiran muslim modernis pada teori kehujjahan hadis kontemporer. Untuk melakukannya, penelitian ini menggali tiga data, yakni teori kehujjahan hadis era klasik, kehujjahan hadis era kontemporer, serta pemikiran-pemikiran muslim modernis. Data pertama digali dari kitab Maḥmūd Ṭaḥḥan, data kedua dari karya al-Idlibī dan Jasser Auda, lalu data ketiga dirangkum dari tiga kitab: karya Aḥmad Amīn, Abū Rayyah, dan al-Sibā’ī. Data pertama dan kedua dianalisis secara komparatif lalu dihubungkan dengan data ketiga yang dianalisis melalui analisis konten. Melalui hal itu, terkonfirmasi bahwa teori kehujjahan hadis kontemporer merupakan imbas dari pemikiran muslim modernis yang meragukan validitas hadis, otoritas Nabi, dan kewahyuan hadis. Dua teori kehujjahan hadis kontemporer muncul sebagai respons kontra dan evaluatif atas tiga tema yang diragukan muslim modernis tersebut.]